JRastro: a trace agent for debugging multithreaded and distributed Java programs - Silva, G. J. da; Schnorr, L. M.; Stein, B. de Oliveira (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2003)
Program tracing is one of the most used techniques to debug parallel and distributed programs. In this technique, events are recorded in trace files during the execution of the program for post mortem visualization of its behavior. We describe JRastro, a trace agent capable of tracing Java programs. The agent was designed to cover three key features: to be transparent to the application developer, to use unmodified Java virtual machines and to observe remote method invocations. By integrating these three features, JRastro differentiates itself from similar tools. Unfortunately, for a complete and clean implementation of RMI visualization, additional support on the Java monitoring system is needed.